APLIKASI “AYAMKU” UNTUK PENDATAAN DAN PELAPORAN HASIL PENJUALAN AYAM POTONG BERBASIS ANDROID - ABDUL AZIS (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Slaughtering the Chicken Pak Pak Agus is a place for cutting broiler chickens that have been established since 2007 and located at Jl. Gunung Galunggung RT 04 RW 06 Pabuwaran, Purwokerto Utara. During this time in conducting sales and payment data collection is still done manually using the only memorandum for orders from restaurants, while for retail buyers do not use memorandum. Some of the difficulties faced are the difficulties in checking the chicken stock, only estimating the weight of the chicken that would be ordered, and also the payment recapitulation which is still written in the memorandum makes many problems in doing addition. To help the process of data collection and reporting of sales results needed a system, an application for data collection and reporting of the sale of broiler chickens based on Android was made. In making this application using Android Studio and using the Waterfall system development method. With this system, it is expected to support the performance of Mr. Agus' Cutting, making it easier to manage the buying and selling data.